PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia periode 2018-2020) - Rosiva, Maulindatur; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
Corporate social responsibility is one of the key attributes that determine reputation and is believed to increase a good reputation for the company. The purpose of this study was to analyze and examine the effect of Corporate Social Responsibility (CSR) Disclosure on firm value through profitability. This research is causality research. The population in this study are conventional banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that Corporate Social Responsibility (CSR) disclosures have a significant positive effect on profitability, Corporate Social Responsibility (CSR) disclosures have a positive but not significant effect on firm value, profitability has a significant positive effect on firm value. The results of the indirect effect hypothesis test show that the variable Corporate Social Responsibility (CSR) Disclosure on firm value through profitability has a significant positive effect.